Functional link between bone morphogenetic proteins and insulin-like peptide 3 signaling in modulating ovarian androgen production - Glister, Claire; Satchell, Leanne; Bathgate, Ross A.D.; Wade, John D.; Dai, Yanzhenzhi; Ivell, Richard; Anand-Ivell, Ravinder; Rodgers, Raymond J.; Knight, Philip G. (National Academy of Sciences, 2013)
Bone morphogenetic proteins (BMPs) are firmly implicated as intraovarian regulators of follicle development and steroidogenesis. Here we report a microarray analysis showing that treatment of cultured bovine theca cells (TC) with BMP6 significantly (>twofold; P < 0.01) up- or down-regulated expression of 445 genes. Insulin-like peptide 3 (INSL3)was themost heavily down-regulated gene (−43-fold)with cytochrome P450, subfamily XVII (CYP17A1) and other key steroidogenic transcripts including steroidogenic acute regulatory protein (STAR), cytochrome P450 family 11, subfamily A1 (CYP11A1) and 3 beta-hydroxysteroid dehydrogenase type 1 (HSD3B1) also downregulated. BMP6 also reduced expression of nuclear receptor subfamily 5A1 (NR5A1) known to target the promoter regions of the aforementioned genes. Real-time PCR confirmed these findings and also revealed a marked reduction in expression of INSL3 receptor, relaxin/insulin-like family peptide receptor 2 (RXFP2). Secretion of INSL3 protein and androstenedione were also suppressed suggesting a functional link between BMP and INSL3 pathways in controlling androgen synthesis. RNAi-mediated knockdown of INSL3 reduced INSL3 mRNA (75%) and protein (94%) level and elicited a 77% reduction in CYP17A1 mRNA and 83% reduction in androstenedione secretion. Knockdown of RXFP2 also reduced CYP17A1 expression (81%) and androstenedione secretion (88%). Conversely, treatment with exogenous (human) INSL3 increased androstenedione secretion ∼twofold. The CYP17A1 inhibitor abiraterone abolished androgen secretion and reduced expression of both INSL3 and RXFP2. Collectively, these findings indicate a positive autoregulatory role for INSL3 signaling in maintaining thecal androgen production, and visa versa. Moreover, BMP6-induced suppression of thecal androgen synthesis may be mediated, at least in part, by reduced INSL3-RXFP2 signaling.